Al-IslÄm wa al-Marâ€™ah: Qaá¸Ä«yat al-Marâ€™ah â€˜inda al-DÄrisÄ«n bi al-JamÄ«â€™at al-IslÄmÄ«yah al-á¸¤ukÅ«mÄ«yah bi IndÅ«nÄ«sÄ«yÄ - Jahroni, Jajang (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
The article's main aim is to map the development of gender discourse in IAIN throughout Indonesia. As is known, the discourse on gender only emerged and began to develop in lndonesia in the early 1990s. Yet, IAIN is not only involved in this movement but also plays a very important role in directing the movement. Many IAIN figures are influential gender activists in lndonesia.DOI:Â 10.15408/sdi.v10i2.632